2004
DOI: 10.1023/b:qure.0000018483.01526.ab
|View full text |Cite
|
Sign up to set email alerts
|

Measuring quality of life in children referred for psychiatric problems: Psychometric properties of the PedsQLTM4.0 generic core scales

Abstract: The PedsQL seems a valid instrument in measuring QoL in children referred for psychiatric problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
145
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(173 citation statements)
references
References 15 publications
(23 reference statements)
25
145
1
2
Order By: Relevance
“…Good reliability and validity were reported for the American [27] and Dutch version [3] of the PedsQL. In this study, the Total score was used; this score is computed by summing the scores for each item.…”
Section: Pediatric Quality Of Life Inventory™ Version 40 (Pedsql)mentioning
confidence: 97%
See 3 more Smart Citations
“…Good reliability and validity were reported for the American [27] and Dutch version [3] of the PedsQL. In this study, the Total score was used; this score is computed by summing the scores for each item.…”
Section: Pediatric Quality Of Life Inventory™ Version 40 (Pedsql)mentioning
confidence: 97%
“…At the first assessment (Time 1), a sample was assessed of 310 children (response rate 73.1 %; mean age 11.3 years; range 6-18 years), who had been referred between August 1, 2000 and September 15, 2001 to a general or a university child psychiatric outpatient department in Rotterdam, The Netherlands. By recruiting patients from these two clinics, children with a broad range of problems, varying from mild to severe, were included [3,5]. At the second assessment (Time 2; mean follow-up time 389 days; SD = 66 days), 231 children and their parents participated (response rate 74.5 %; mean age 12.2 years; range 7-19 years).…”
Section: ■ Procedures and Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that QoL in children with psychiatric disorders is not only considerably poorer than that of children from the general population, but also comparable to or even poorer than that of physically ill children [1][2][3], indicating that there is an association between poor QoL and child psychopathology. These findings underscore the need for QoL assessment in children with psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%